1999
DOI: 10.1161/01.atv.19.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Peripheral Arterial Disease Are Independent Predictors of Cardiovascular and All-Cause Mortality, Especially Among Hypertensive Subjects

Abstract: Abstract-Microalbuminuria (MA) is associated with increased cardiovascular and all-cause mortality. It has been proposed that MA reflects generalized atherosclerosis and may thus predict mortality. To investigate this hypothesis, we studied the associations between, on the one hand, MA and peripheral arterial disease (PAD), a generally accepted marker of generalized atherosclerosis, and, on the other hand, cardiovascular and all-cause mortality in an age-, sex-, and glucose tolerance-stratified sample (nϭ631) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
251
1
30

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(294 citation statements)
references
References 50 publications
12
251
1
30
Order By: Relevance
“…14 In hypertensive subjects, albumin-to-creatinine ratios of 10-16 mg mg À1 , 2.5-to 3-fold lower than the cutoff for defining microalbuminuria, predicted increased risk of cardiovascular mortality. 7 Such a low level of albuminuria was also found to predict progression to hypertension in non-diabetic, non-hypertensive subjects, 22 and was associated with a 2.3 times greater adjusted risk of developing ischaemic heart disease. 21 In middle-aged non-hypertensive, nondiabetic Framingham Offspring Study participants, 26 those with an albumin-to-creatinine ratio of X3.9 mg mg À1 for men and X7.5 mg mg À1 for women, well below the threshold for microalbuminuria, experienced a nearly three-fold risk of cardiovascular disease ( Table 1).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…14 In hypertensive subjects, albumin-to-creatinine ratios of 10-16 mg mg À1 , 2.5-to 3-fold lower than the cutoff for defining microalbuminuria, predicted increased risk of cardiovascular mortality. 7 Such a low level of albuminuria was also found to predict progression to hypertension in non-diabetic, non-hypertensive subjects, 22 and was associated with a 2.3 times greater adjusted risk of developing ischaemic heart disease. 21 In middle-aged non-hypertensive, nondiabetic Framingham Offspring Study participants, 26 those with an albumin-to-creatinine ratio of X3.9 mg mg À1 for men and X7.5 mg mg À1 for women, well below the threshold for microalbuminuria, experienced a nearly three-fold risk of cardiovascular disease ( Table 1).…”
mentioning
confidence: 93%
“…[1][2][3][4][5] There is substantial evidence to indicate that UAE in the microalbuminuria range is an independent risk factor for kidney and cardiovascular disease, and of mortality in type 1 and type 2 diabetes mellitus, [1][2][3][4][5][6] hypertensive subjects, non-diabetic subjects, as well as in the general population. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, recent studies conducted in type 2 diabetic patients revealed that even very low UAE rates, below those conventionally accepted as the lower limit to define microalbuminuria (o30 mg per 24 h), were also associated with increased mortality. 15 Similarly, in non-diabetic subjects, albuminuria of o30 mg day À1 was found associated with older age, male gender, smoking, obesity, elevated blood pressure, left ventricular hypertrophy, dyslipidaemia, hyperinsulinaemia, salt sensitivity, lack of nocturnal BP dipping [15][16][17][18][19] and increased risk of coronary heart disease and death 10,15,[20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 99%
“…5,6 Moreover, microalbuminuria is independently associated with increased cardiovascular risk factors and cardiovascular morbidity. 8,9 Therefore, in this study, we investigated the prevalence of RAS and clinical factors related to RAS in Japanese patients with PAD independent of hemodialysis. We also examined various risk factors for CKD based on evaluation of eGFR or urinary microalbumin (MA) in patients with PAD.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In addition to the underlying primary pathological state, several factors, such as lifestyle, socioeconomic status (SES), and occupational exposures, were suggested to modify the progression and outcome of kidney diseases and may be responsible, in part, for the disproportionately high rates of end-stage renal disease in such subgroups as racial/ethnic minorities. [6][7][8][9][10] African Americans were reported to have greater rates of proteinuria.…”
mentioning
confidence: 99%